Gambaran Status Gizi dan Perkembangan Motorik Anak Usia 3-5 Tahun Di Kelurahan Pulutan, Salatiga - Adhe Restu Ananda; Sanfia Tesabela Messakh; Dary (Jurnal Sains dan Kesehatan, 2020)
Abstract Malnutrition of children is still a big problem in Indonesia. Malnutrition refers to an imbalance or lack of energy and nutritional intake in a person. In this case, it can cause health problems for children if this thing happens continuously. The balances between energy and protein intake are very important for the human body. So, if the required energy and nutritional intake are not met, it can inhibit the growth and development of children, especially in motor development. Delays in children's development occur when the structural and functional of children's brains have changed or been harmed. The aim of this study is to determine the ideal nutritional status and motor development of children at 3-5 years of age this research was conducted in Pulutan Village, Central Java, Indonesia. In this study, a quantitative descriptive method using nutritional status data instruments based on Z-Score, the form of Denver Developmental Screening Test II (DDST II) 10 minutes and a questionnaire to collect other data in the form of demographic data (parent data, child data and anthropometric measurements), and a questionnaire were used It was distributed to 98 children represented by their respective parents. The results showed the ideal children's weight in Pulutan Village, Salatiga based on the BB/U index of 85 children, while in the TB/U index there were 86 children of normal height. Based on the results of the DDST II form, there are 60 children having normal fine motor development and 67 children having normal gross motor development. Based on the results of the study, it can be concluded that the description of the nutritional status and development of children in the Pulutan Village, Salatiga mostly has the appropriate developmental growth. Abstrak Kondisi gizi kurang masih menjadi masalah kesehatan di Indonesia. Gizi kurang adalah kurangnya asupan energi dan protein dalam periode waktu lama sehingga membawa dampak negatif pada kesehatan anak. Apabila asupan energi dan protein tidak terpenuhi, pencapaian pertumbuhan dan perkembangan salah satunya perkembangan motorik yang baik pada anak dapat terhambat. Tujuan dari penelitian ini adalah untuk mengetahui gambaran status gizi dan perkembangan motorik anak yang ideal pada usia 3-5 tahun di Kelurahan Pulutan, Salatiga. Metode yang digunakan dalam penelitian ini adalah kuantitatif deskriptif dengan instrument data status gizi berdasarkan WHO Z-Score, form Denver Developmental Screening Test II (DDST II) 10 Menit serta kuesioner untuk mengumpulkan data lainya berupa data demografi (data orang tua, data anak dan pengukuran antropometri). Kuesioner disebarkan pada 98 anak yang diwakilkan oleh orang tua. Hasil penelitian menunjukan berat badan anak yang ideal di Kelurahan Pulutan, Salatiga berdasarkan indeks BB/U yaitu sebanyak 85 anak, sedangkan pada indeks TB/U terdapat 86 anak memiliki tinggi yang normal. Berdasarkan hasil form DDST II menunjukkan ada 60 anak memiliki perkembangan motorik halus yang normal dan 67 anak memiliki perkembangan motorik kasar yang normal. Berdasarkan hasil penelitian, dapat disimpulkan bahwa gambaran status gizi dan perkembangan anak di Kelurahan Pulutan, Salatiga sebagian besar memiliki pertumbuhan perkembangan yang sesuai dengan usia anak.